Physico-chemical comparison of Four commercially available mineral trioxide aggregates = Comparación fisicoquímica de cuatro mineral trióxido agregados disponibles comercialmente - Montero Aguilar, Mauricio 1978-; Vega Baudrit, José Roberto 1966-; Pereira Reyes, Reinaldo 1955-; Pozos Guillén, Amaury de Jesús; Ulate Rodríguez, Esteban 1979- (2023)
To compare the physicochemical composition of 4 MTAs commercially available in Latin America. ProRoot MTA (Dentsply, USA), MTA Angelus (Angelus, Brazil), MTA Flow (Ultradent, USA), and MTA Viarden (Viarden, Mexico) were physically and chemically compared. Scanning electron microscopy (SEM) images were obtained from the MTA powder and the prepared presentations. Energy Dispersive X-Ray Spectroscopy (EDS) analyses were performed by triplicate, to calculate the mass proportion of calcium (Ca), silicon (Si), the Ca/Si proportion among the 4 brands. Thermogravimetric analyses (TGA) were conducted (50ºC-1000ºC), and mass loss and inflection points were calculated for each material. Statistical differences for Ca and Si content were determined by ANOVA (p<0.05). SEM images showed evident differences in the appearance of both the powder and the prepared MTAs among brands. Angelus MTA showed cubic prisms not observed in the other 3 brands. ProRoot MTA and MTA Flow showed similar homogeneous structures. MTA Viarden was the less homogeneous, with random structures (>15um). When comparing the mass proportions of Ca and Si between the 4 powder samples, MTA Viarden showed a significantly lower proportions of both elements when compared with the other brands (p<0.005). TGA analysis showed a similar behavior for ProRoot MTA, MTA Angelus and MTA Flow, with less than 2% mass loss when the 1000C temperature was reached. MTA Viarden showed a mass loss of 9,94% before the 700C, indicating the presence of different content sensible to temperature degradation. The analyzed MTAs demonstrated to vary significantly in their chemical composition and physical characteristics. Clinicians must be aware of the differences between different brands of a same material, and future research should focus on the clinical implications of these differences.
Comparar la composición fisicoquímica de 4 MTA disponibles comercialmente en América Latina. Se compararon física y químicamente ProRoot MTA (Dentsply, EE. UU.), MTA Angelus (Angelus, Brasil), MTA Flow (Ultradent, EE. UU.) y MTA Viarden (Viarden, México). Se obtuvieron imágenes de microscopía electrónica de barrido (SEM) del polvo de MTA y de las presentaciones preparadas. Los análisis de espectroscopía de dispersión de energía de rayos X (EDS) se realizaron por triplicado para calcular la proporción de masa de calcio (Ca), silicio (Si), la proporción Ca/Si entre las 4 marcas. Se realizaron análisis termogravimétricos (TGA) (50ºC-1000ºC), y se calcularon las pérdidas de masa y los puntos de inflexión para cada material. Las diferencias estadísticas para el contenido de Ca y Si se determinaron mediante ANOVA (p<0,05). Los análisis SEM mostraron diferencias evidentes en la apariencia tanto del polvo como las preparaciones de los MTA, entre las diferentes marcas. MTA Angelus mostró prismas cúbicos no observados en las otras 3 marcas. ProRoot MTA y MTA Flow mostraron estructuras homogéneas similares. MTA Viarden fue el menos homogéneo, con estructuras aleatorias (>15um). Al comparar las proporciones de masa de Ca y Si entre las 4 muestras de polvo, MTA Viarden mostró proporciones significativamente más bajas de ambos elementos en comparación con las otras marcas (p<0,005). El análisis TGA mostró un comportamiento similar para ProRoot MTA, MTA Angelus y MTA Flow, con menos del 2 % de pérdida de masa al alcanzar los 1000 °C de temperatura. El MTA Viarden mostró una pérdida de masa de 9,94% antes de los 700 °C, indicando la presencia de diferentes contenidos sensibles a la degradación por temperatura. Los MTA analizados demostraron diferencias significativas en su composición química y características físicas. Los clínicos deben ser conscientes de las diferencias entre las diferentes marcas de un mismo material...
En revista Odóvtos, vol. 25, no.3 (septiembre-diciembre 2023)
Descripción basada en el contenido visto el 17 de enero, 2025
También disponible en formato HTML y EPUB